Fotos en el congelador : novela - García-Roméu, Carmen (Madrid : Editorial Verbum, 2015)
Inma, a frustrated author, is forced to move in with her grandfather because she can't support herself. She is a finalist in a literary contest, but the judges have decided to leave the prize vacant. Her grandfather, who specializes in past life regressions, decides to put the photos of the contest judges in the freezer to keep them from doing her more harm. From that moment on, things improve for Inma.
Novel.
"Finalista del Premio Iberoamericano Verbum de Novela, 2014"--Cover.
Online resource; title from PDF title page (Digitalia, viewed October 5, 2016)
Keywords: Authors -- Fiction; Grandparent and child -- Fiction; Novels; Electronic books